Worker Queens? Behavioral Flexibility of Queens in the Little Fire Ant Wasmannia auropunctata - Ortiz-Alvarado, Yarira; Rivera-Marchand, Bert (Frontiers in Ecology and Evolution, 2020)
Many species of social hymenoptera demonstrate behavioral flexibility, where older workers that typically forage can revert to younger worker tasks, such as nursing, when these are absent. This flexibility is typical of the sterile worker class, yet rare in queens. In the little fire ant (Wasmannia auropunctata) queens have been reported to perform only egg laying. We examined behavior of queens of W. auropunctata after demographic manipulation. When half of the workers were removed from the colony, queens were observed caring for eggs, larvae and pupae as well as eating outside of the nest, like forager workers. We examined the relationship between these atypical queen behaviors and their juvenile hormone binding protein (JHbp) and vitellogenin (Vg) expression via QRT-PCR method. JHbp and Vg expression decreased when queens were performing worker tasks, resembling the expected expression pattern of typical sterile workers. Flexibility in queen behaviors in the little fire ant may be an important adaptation to changing environments. As a significant invasive species, such adaptation may increase the probability of colony survival during propagation. Our results not only present new insights in behavioral flexibility in social insects, but also increases our understanding of the success of this significant invasive species.